Molecular mechanism of LncRNA MALAT1 in regulating hepatocellular carcinoma progression via the miR-383-5p/PRKAG1 axis and its role in the tumor immune microenvironment - Zhang, Rui; Li, Mingze; Lu, Shan; Wang, Anni; Zhang, Shujun (Frontiers in Oncology, 2025)
BackgroundHepatocellular carcinoma (HCC) is a highly prevalent malignant tumor worldwide, and its development is closely associated with dysregulated non-coding RNA expression. The long non-coding RNA MALAT1 is overexpressed in multiple cancers, but its precise mechanistic role and downstream regulatory network in HCC remain incompletely understood. Additionally, PRKAG1, a regulatory subunit of AMPK, has an unclear function in tumor progression. This study aimed to investigate the role and clinical significance of the MALAT1-PRKAG1 axis in HCC pathogenesis.MethodsA multi-omics approach was employed to systematically dissect the mechanism of the MALAT1-PRKAG1 axis in HCC. Bioinformatics analysis using GEPIA2 and TCGA databases revealed that MALAT1 and PRKAG1 were significantly upregulated in HCC and correlated with poor prognosis. Cellular experiments demonstrated that knockdown of MALAT1 or PRKAG1 suppressed HCC cell proliferation, migration, and invasion. Mechanistic studies indicated that MALAT1 upregulates PRKAG1 expression by competitively binding miR-383-5p. Further analyses showed that PRKAG1 remodels the tumor immune microenvironment by modulating immune cell infiltration (CIBERSORT analysis) and intercellular communication (single-cell RNA sequencing), while also activating key pathways such as the cell cycle and DNA repair (GO/KEGG enrichment analysis).ResultsThis study uncovered the critical role of the MALAT1-PRKAG1 regulatory axis in HCC. MALAT1 was significantly overexpressed in HCC tissues and cell lines, and its expression was associated with poor patient prognosis. Knockdown of MALAT1 markedly inhibited HCC cell proliferation, migration, and invasion. PRKAG1, as a downstream target of MALAT1, was also highly expressed in HCC and correlated with tumor stage and adverse outcomes. Mechanistically, MALAT1 competitively binds miR-383-5p to relieve its suppression of PRKAG1, thereby activating the P53 and AKT signaling pathways. Additionally, PRKAG1 modulated immune cell infiltration (particularly CD4+ T cells and M0 macrophages) and promoted intercellular communication via the MIF signaling network. Multi-omics analysis revealed that PRKAG1-associated genes were primarily enriched in critical pathways, including the cell cycle and DNA repair, collectively driving HCC progression.ConclusionThis study elucidates the oncogenic role of the MALAT1/miR-383-5p/PRKAG1 axis in HCC, demonstrating that PRKAG1 promotes tumor progression by regulating cell proliferation, the immune microenvironment, and key signaling pathways. These findings provide potential novel targets for HCC prognosis assessment and targeted therapy.